The impact of the national stay-at-home order on emergency department visits for suspected opioid overdose during the first wave of the COVID-19 pandemic. (1st November 2021) - Root, Elisabeth D.; Slavova, Svetla; LaRochelle, Marc; Feaster, Daniel J.; Villani, Jennifer; Defiore-Hyrmer, Jolene; El-Bassel, Nabila; Ergas, Rosa; Gelberg, Kitty; Jackson, Rebecca; Manchester, Kara; Parikh, Megha; et al.
Highlights: Declaration of the COVID-19 national public health emergency impacted emergency department encounters for opioid overdose. An immediate decline in ED rates for opioid overdose occurred after March 14, 2020 in New York, Massachusetts, and Ohio. Kentucky and Ohio saw a significant increase in opioid overdose after the emergency declaration. The impact of the COVID-19 pandemic on encounters for suspected opioid overdose was highly heterogeneous across the 4 states. Abstract: Background: Although national syndromic surveillance data reported declines in emergency department (ED) visits after the declaration of the national stay-at-home order for COVID-19, little is known whether these declines were observed for suspected opioid overdose. Methods: This interrupted time series study used syndromic surveillance data from four states participating in the HEALing Communities Study: Kentucky, Massachusetts, New York, and Ohio. All ED encounters for suspected opioid overdose (n = 48, 301) occurring during the first 31 weeks of 2020 were included. We examined the impact of the national public health emergency for COVID-19 (declared on March 14, 2020) on trends in ED encounters for suspected opioid overdose. Results: Three of four states (Massachusetts, New York and Ohio) experienced a statistically significant immediate decline in the rate of ED encounters for suspected opioid overdose (per 100, 000) after the nationwide public health emergency declaration (MA: -0.99; 95 % CI: -1.75, -0.24; NY: -0.10; 95 % CI, -0.20, 0.0; OH: -0.33, 95 % CI: -0.58, -0.07). After this date, Ohio and Kentucky experienced a sustained rate of increase for a 13-week period. New York experienced a decrease in the rate of ED encounters for a 10-week period, after which the rate began to increase. In Massachusetts after a significant immediate decline in the rate of ED encounters, there was no significant difference in the rate of change for a 6-week period, followed by an immediate increase in the ED rate to higher than pre-COVID levels. Conclusions: The heterogeneity in the trends in ED encounters between the four sites show that the national stay-at-home order had a differential impact on opioid overdose ED presentation in each state.